2020
DOI: 10.1017/s1751731119002143
|View full text |Cite
|
Sign up to set email alerts
|

Invited review: Tannins as a potential alternative to antibiotics to prevent coliform diarrhea in weaned pigs

Abstract: In addition to a multifactorial etiology of nutritional, social and environmental stressors, post-weaning diarrhea (PWD) in pigs is often related to infection with specific pathogens such as enterotoxigenic Escherichia coli (ETEC). In swine farming operations, the incidence of PWD is a global concern and is associated with an unbalanced gut status, resulting in poor performance and high antimicrobial consumption via prophylaxis and metaphylaxis. Increases in antimicrobial resistance are reinforcing an already-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 65 publications
(106 reference statements)
1
76
0
1
Order By: Relevance
“…In fact, tannins can inhibit the growth of some pathogenic bacterial species (e.g., E. coli) without affecting the physiological growth and proliferation of probiotic lactic acid bacteria, which have a positive effect at the intestinal level [33]. This selective effect may be an advantage in the use of tannins in feed.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, tannins can inhibit the growth of some pathogenic bacterial species (e.g., E. coli) without affecting the physiological growth and proliferation of probiotic lactic acid bacteria, which have a positive effect at the intestinal level [33]. This selective effect may be an advantage in the use of tannins in feed.…”
Section: Discussionmentioning
confidence: 99%
“…Commensal bacteria such as Bifidobacterium breve or Lactobacillus salivarius are very useful and their growth or presence should not be inhibited by the tannin. Kamijo et al [ 115 ] reported that ellagitannins isolated from Rosa rugose petals have some antibacterial activities against pathogenic bacteria such as Salmonella sp, Bacillus cereus , S. aureus and E. coli but they had no effect on beneficial bacteria. Most in vitro results are supported by in vivo experiments that the inclusion of tannin in monogastric animals can lower the occurrence and severity of diarrhea [ 116 ].…”
Section: Health Benefits Of Tannins In Monogastric Animal Productmentioning
confidence: 99%
“…The well-known antimicrobial resistance caused by the misuse of antibiotics drugs in animal production, and the EU ban on their in-feed use (Regulation EC/1831/2003) has led to an increase in the incidence of livestock disease and economic damage. For several years, research has dedicated great efforts to investigating alternatives able to sustain production without causing an increase of antimicrobial resistance and several natural products have been investigated [11,12].…”
Section: Introductionmentioning
confidence: 99%